Mapping Riset Auditing dengan Analisis Bibliometric - Sherliani, Deska (Jurnal Etnik: Ekonomi-Teknik, 2021)
Studying accounting or auditing issues from various previousstudies will be able to open new opportunities to find more variedresearch and to get updates from a study, it is necessary to analyzeprevious research by mapping related research in the field ofauditing. This study aims to conduct research related to the field ofauditing published in various international journals from 2016-2021.This study uses a bibliometric analysis method which consists ofdefining search keywords, namely 'auditing', (2.) initial searchresults, (3.) narrowing of search results, (4.) preparation of initialdata statistics, and (5.) data analysis. The findings of the study were488 articles from 17 publishers, the most published articles relatedto auditing were published by the publishing agency 'Springer'. Themost published articles occurred in 2020 as many as 95 articles.While the most cited article citations in 2019 were 824 with 85articles and the most citations per author occurred in 2017 as manyas 1102 with 78 articles. Based on the results of the research that hasbeen done, it can be concluded that research on auditing hasincreased every year and has become a big concern, this can be seenfrom the results of the publications that are most widely publishedin the journals of Springer and Elsevier.